APPROACHES AND METHODS EMPLOYED IN REVITALISING THE SEPEREWA MUSICAL TRADITION IN GHANA - Agyefi, Papa Kow Mensah (International Library of African Music, 2023)
This article examines how Osei Korankye, a seperewa (a west African harp) player in Ghana, managed to thrive in an often unfavourable environment for traditional musicians. The seperewa is a Ghanaian harp with a likeness to the kora. The article examines Korankye’s efforts to preserve and restore local interest in seperewa music. The conflict between traditional musical practices and the multiplicity of sounds and ideologies brought by globalisation and cultural imperialism after contact with Europe in the fifteenth century is critical to the discourse in this article. As a result of these encounters, Ghanaian communities have lost much of their musical traditions; those remaining are cherished by a small number of individuals. Many see such traditions as a building block to most of Ghana’s cultural heritage, hence the call for cultural revitalisation in many quarters. Drawing on the available literature and ethnographic interviews, I position Korankye, and his methods, as a powerful example of such a strategy for revitalisation while outlining many of the struggles he negotiated. This article corroborates existing arguments made by many that globalisation and cultural imperialism profoundly influenced African civilisations, threatening a loss of contact between communities and their customs.
Keywords: Sustainability; Culture; Musical instruments; Folk music; Globalisation; Revitalisation; Traditional Music; Seperewa (Instrument); Indigenous Music; Cultural Imperialism; African Music; Ghana